To pray or to prey breaking the silence of lay servers' sexual encounters with catholic priests. - Aguilar, Joan F.; Fabillar, Dee Ann L.; Fernandez, Abegail D. (Joan Aguilar, 2012)
This is a qualitative study which focuses on the sexual encounters between priests and lay servers from the viewpoint of the victim. The researchers sought to: (a) determine the relationship between the priest and the lay server before the occurrence of the sexual act; (b) identify factors facilitating the occurrence of the sexual act between the priests and the lay server; (c) determine the reactions of the participants upon the occurrence of the sexual act; (d) determine the psychological effects of the sexual encounters on the participants according to the domains: Cognition, Emotion, Behavior, and Social Interaction; (e) identify the coping mechanisms used by the lay servers; and (f) determine the present state of the lay servers' lives. Data was gathered through personal interviews, either face-to-face or by proxy as the topic was considered to be a sensitive issue. Eleven (11) lay servers served as respondents who were seminarians, ex-seminarians, altar servers, and ex-altar servers. Results showed that: most of the sexual encounters were facilitated by the following factors: curiosity, debt of gratitude, learned helplessness and the influence of alcohol. In terms of cognition, results showed that the lay servers lost their respect and trust towards the priests who initiated the sexual encounters. Majority of the respondents who were emotionally affected felt guilty for not being able to stop the occurrence of the sexual acts. The prominent behavioral change is the disinterest in attending mass. In terms of the social interactions, majority of the lay servers maintained their existing relationships with people. The five seminarians however became loners and became suspicious of people. It can be inferred that priests usually initiate the sexual encounters with lay servers who have reached puberty and whom they formed a close relationship with and that there are varying factors among which sexual encounters are facilitated which in turn result to significant changes in the cognitive, emotional, behavioral, and interpersonal aspect of the lay servers' lives. It is thus recommended that the Catholic Church should directly address the issue of clerical transgression instead of keeping it from the public to preserve its image.